Simental Süt İneklerinde Tırnak Bozukluklarının Süt Üretimine Etkisi - ZLATANOVIĆ, Zvonko; HRISTOV, Slavča; STANKOVIĆ, Branislav; CINCOVIĆ, Marko; NAKOV, Dimitar; BOJKOVSKI, Jovan (Kafkas University, 2020)
A study on claw disorders’ infl uence on milk production was performed during one year on 226 Simmental loose-reared cows. The first trial group included 42, the second 37, and the third 34 cows, with claw changes observed in the first hundred days of lactation, between days 101 and 200, between days 201 and 305, respectively. The control group included 113 cows with no observed changes. Lameness intensity was assessed once a week. Milk yield data were collected three weeks before, in the week of treatment of claws and three weeks afterwards. There were significantly more cows with lameness in the third group than in the other two groups, as well as the most cows with one aff ected limb in the first hundred days of the lactation (P<0.05). Significantly fewer cows with two aff ected limbs were present in the first group. In the second group, more cows were observed with two affected limbs than in the first group (P<0.05). In the third group, more cows with three or four affected limbs were noticed than in the other groups. The most common claw disorders were: solar ulcer, laminitis, dermatitis digitalis and overgrown claws. Cows whose claws were aff ected between days 101 and 200 of lactation period produced 231 kg less milk than those of the control group; cows whose claws were affected in the last third of lactation produced 26 kg less milk. Nevertheless, no significant differences were found between milk yields of the control and trial groups (P>0.05). Cows affected in the first third of lactation produced less milk (324 kg) than both healthy and cows with claw changes manifested in later stages of lactation. Obtained data confirm that claw disorders may affect dairy production.
Keywords: Claw disorders, Cow, Lameness, Milk production, Simmental